Dinamika Proses Promosi Jabatan di Lingkungan Pemerintah Provinsi Kalimantan Barat - Rusdiono Rusdiono; Ira Patriani; Ahirul Habib Padilah (Journal of Social and Policy Issues, 2022)
This paper examines the dynamics of the promotion process within the West Kalimantan Province's administrative structure. This essay's main concern is with laws and rules that have carefully and objectively governed the public bureaucracy's promotion system. The data are secondary data from numerous books, journals, internet news sources, and scientific papers. The method is qualitative with a descriptive approach. Data were gathered and examined from the various literatures. The study's findings show that the West Kalimantan Provincial Government's promotion system continues to give priority to traditional, structural, and patrimonial values, leaving employees who receive promotions in a powerless position with no leverage when negotiating with superiors. The study's finding is that Indonesia has only just begun to implement contemporary bureaucracy, and that it has not fully integrated its values.